Daily Recovery Experiences of Japanese Small Business Owners and the Link with Well-Being and Ill-Being - Roy Thurik; Masatoshi Kato; Peter van der Zwan; Chihiro Kageura (Institute of Labor Economics (IZA), 2025)
Numerous studies deal with the link between daily recovery experiences (DRE) and mental health for employees. Hardly any studies exist for small business owners. This is surprising given that their health is not just important for themselves but also for their environment (such as employees, clients, suppliers, networks). In the present study we analyse if this link also works for some 2,400 Japanese small business owners. Next to overall DRE, four dimensions of DRE are distinguished (detachment, relaxation, mastery, and control). Mental health is captured using well-being (psychological well-being and job satisfaction) and ill-being (burnout and stress). First, we compare our DRE levels with many other (employee) studies. Second, controlling for many phenomena including participating in nomikai (a typical Japanese custom of getting together after office hours), we show that the quality of overall DRE is positively linked to well-being, and negatively to ill-being. Third, like the quality of overall DRE, nomikai activities of the owner are positively linked to their psychological well-being and job satisfaction, and negatively to burnout and stress. Its role seems to be independent of that of the quality of DRE.
Keywords: I12; I31; L26; 330; small business owners/managers; entrepreneurs; daily recovery experiences; Nomikai; well-being; job satisfaction; burnout; stress; Japan